Optimal slope and azimuth analysis for photovoltaic panels based on solar radiation in Kashan - Ali Reza rahimi; Ali Reza Karbalaee doree; mohammad reza karbalaee (تحقیقات کاربردی علوم جغرافیایی)
One of the most important parameters in maximal use of radiant energy is the proper deployment of photovoltaic. The purpose of this study was to determine the optimum setting and tilt for installing photovoltaic panel in Kashan city. For this purpose, using the Masters Gilbert physical relations and relationships, the radiation received on the surface of the panel is calculated. The results of this study indicate that the amount of radiation received on the collector's surface in the south and in different slopes, 64 percent of the time of year, is more than the radiation on the panel surface mounted in the direction of the southeast or west with different slope angles. The highest amount of radiation is in the Azimuth to the south at a gradient of 30 degrees and 40 degrees; Southwest Azimuth (30 degrees) is almost similar to the South Azimuth and only in the southeast west, in summer, glides near the verge, they receive more radiation than the south. The amount of radiation received on the surface of the panel in the direction of south east west (Azimuth 60 °) on different slopes in 87% of the year is greater than the radiation on the panel surface mounted east or west (90 ° azimuth) with different slope angles. By comparing the results, it turns out that the direction of the photovoltaic panel installation will change, as the south changes to the east or west, the intensity of radiation will decrease in the days of the year. The highest photovoltaic energy output in Kashan is in the direction to the south, and with the angle of installation of photovoltaic panel 30 degrees from the horizon line. The most suitable slope for mounting panels between 30 and 40 degrees was obtained from other slopes.